VIOLATION OF SPELLING AND STYLE NORMS IN SOCIAL NETWORKS: CAUSE AND CONSEQUENCES - Mardonova Marg'uba Boboyorovna (Ecominds Press, 2026)
This article analyzes the causes, forms and con sequences of violations of spelling Uzbek language in social networks. The study examines linguistic transformations such as transliteration, phonetic spelling, abbreviations, and emotive symbols. The results show that online communication significantly influences youth speech culture and literary language norms.
Keywords: Social, networks, spelling norms, stylistic norms, internet language linguistic transformation, speech culture.